Empirical Musicology: Aims, Methods, Prospects - Clarke, Eric F.; Cook, Nicholas (Oxford Oxford University Press, 2004)
The study of music is always, to some extent, "empirical," in that it involves testing ideas and interpretations against some kind of external reality. But in musicology, the kind of empirical approaches familiar in the social sciences have played a relatively marginal role, being generally restricted to inter-disciplinary areas such as psychology and sociology of music. Rather than advocating a new kind of musicology, Empirical Musicology provides a guide to empirical approaches that are ready for incorporation into the contemporary musicologist's toolkit. Its nine chapters cover perspectives from music theory, computational musicology, ethnomusicology, and the psychology and sociology of music, as well as an introduction to musical data analysis and statistics. This book shows that such approaches could play an important role in the further development of the discipline as a whole, not only through the application of statistical and modeling methods to musical scores but also--and perhaps more importantly--in terms of understanding music as a complex social practice.
Keywords: 20th Century (1901-2000); 21st Century (2001-2100); Musicology; Empiricism